(untitled) (Fiep Bulletin - online, 2012)
In our society we can see the grow of chronic non-communicable diseases and eating disorders in the young people due lack of physical activity, poor eating habits and midia influences saying to eat fast food that are faster and practical, but without the nutrients required. Against the difficulties of changing habits of teenagers, physical education teachers have to talk about themes to stimulate the students to know and take care about themselves. So, the objective of this study was to check if these themes are able to reduce body mass index and stimulate the practice exercises and better eating habits. We use the measure body mass index to classify the nutritional status of students and applied a questionnaire focused on physical activity and eating habits. The intervention occurred through themes facing the health. Through a reassessment of BMI and the questionnaire applied we conclude that health education produces significant results in quality of life.